Gardens of the Bible as a Place of Encounter between Man and God - Wawrzyniak, Justyna (Studia Ecologiae et Bioethicae, 2022)
This article combines two goals. The first is to show the gardens of the Bible as the background settings for the most important encounters between God and man, and the second is to define the genius loci of these places. The challenge was to isolate the physical features of the gardens of the Bible as carriers of spiritual aspects. The introduction presents the role of nature and the garden as the theatre of God’s Glory (mentioned by Calvin). It explores moreover the sacred aspects of historical gardens and then describes the nature of individual gardens of the Bible and the events that took place there, closing with the results of observations ordered by parameters that make up the western-defined genius loci (spirit of the place), such as: things, earth, sky, order, and character. At the end of each description of a garden, the challenge of defining its spirit was taken for the first time. The inspiring phenomenon of gardens and the conscious use of selected elements will meet not only aesthetic expectations but also the spiritual exploration of contemporary people.